THE USE OF INTERACTIVE MULTIMEDIA IN LEARNING BASED ON DISRUPTION ERA AT ELEMENTARY SCHOOL - Widyawulandari, Rizki; Sarwanto, Sarwanto; Indriayu, Mintasihu (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The disruption era is defined as the time when so many innovations are emerging, unrecognized by established organizations that they interfere with the activities of the old system's order or even destroy the old system. The world of education must also be ready in the face of this disruption era, especially in the era of increasingly advanced technology. One of the efforts in the development of learning-based disrupted era, especially in primary school is the use of interactive multimedia. With the steps and processes of using the right interactive multimedia, using interactive multimedia as a message media will stimulate the thoughts, feelings, concerns and desires of students so as to encourage more interactive and communicative learning process and can improve the learning experience of students become more concrete. The research method used is qualitative with case study design where researchers collect and analyze data about the use of interactive multimedia in primary school. The results revealed that interactive multimedia is considered important in the effort of IT utilization in learning in disruption era but there are still many teachers who have not realized and apply it.